Legionnaires’ disease Surveillance in Italy (Italian Journal of Public Health, 2004)
In the report presented, data on legionellosis diagnosed in the year 2003 in Italy and notified to the National Surveillance System are analysed. Overall, 617 cases were notified, of which 517 were confirmed and 46 were presumptive.The characteristics of the patients are very similar to those reported in the previous years in terms of male/female ratio, age–specific distribution, occupation, etc. Legionella pneumophila serogroup 1 was responsible for approximately 90% of the cases.